2002
DOI: 10.1037/0278-7393.28.5.951
|View full text |Cite
|
Sign up to set email alerts
|

Strategic effects in associative priming with words, homophones, and pseudohomophones.

Abstract: G. Lukatela and M. T. Turvey (1994a) showed that at a 57-ms prime-presentation duration, the naming of a visually presented target word (frog) is primed not only by an associate word (toad) but also by a homophone (towed) and a pseudohomophone (tode) of the associate. At a 250-ms prime presentation, priming with the homophone was no longer observed. In Experiment 1, the authors replicated these priming effects in the Dutch language. Next, the authors extended the priming paradigm to a word/legal-nonword lexica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 45 publications
(141 reference statements)
6
44
1
5
Order By: Relevance
“…Thus, it is possible that priming effects are somewhat different than the types of effects that Pexman and colleagues (Pexman & Lupker, 1999;Pexman et al, 2001) were investigating (e.g., homophone effects and polysemy effects). Consistent with this idea, in a recent study, Drieghe and Brysbaert (2002) also found that masked semantic/ associative priming effects did not increase in size with pseudohomophones versus standard nonwords. In contrast, Joordens and Becker (1997) did report larger semantic priming effects with pseudohomophonesthan with standard nonwords in their Experiment 2, although not in their Experiment 1.…”
Section: Resultssupporting
confidence: 64%
“…Thus, it is possible that priming effects are somewhat different than the types of effects that Pexman and colleagues (Pexman & Lupker, 1999;Pexman et al, 2001) were investigating (e.g., homophone effects and polysemy effects). Consistent with this idea, in a recent study, Drieghe and Brysbaert (2002) also found that masked semantic/ associative priming effects did not increase in size with pseudohomophones versus standard nonwords. In contrast, Joordens and Becker (1997) did report larger semantic priming effects with pseudohomophonesthan with standard nonwords in their Experiment 2, although not in their Experiment 1.…”
Section: Resultssupporting
confidence: 64%
“…We first replicated the masked associative priming effect with word primes previously reported by Lukatela and Turvey (1994) and Drieghe and Brysbaert (2002):…”
Section: Discussionsupporting
confidence: 56%
“…For instance, Lukatela and Turvey (1994) reported that the naming latency for the target word "frog" was 20 ms faster when it was primed by "TOAD" than when it was primed by "TOLLED". Drieghe and Brysbaert (2002) repeated this finding and extended it to a lexical decision task (i.e., participants had to decide whether the target stimulus was a word or not). Alameda, Cuetos, and Brysbaert (2003) further showed that associative priming is not limited to words, but can also be observed with numbers as targets (e.g.…”
Section: Research On Acronyms Recently Knew a Small Revival With The mentioning
confidence: 98%
“…On the other hand, this attentional and task-dependent account has been questioned by findings from a number of psycholinguistic studies that reported phonological and semantic effects in visual word recognition even when these representations were totally irrelevant to the task or not directly accessible (Rodd, 2004;Tanenhaus et al, 1980;Ziegler and Jacobs, 1995), thus supporting the claim of an automatic and possibly mandatory access to phonology and meaning during reading (Frost, 1998). Similarly, masked priming studies showed that shared phonological and semantic representations between a prime and a target affect recognition of the target even in the absence of prime awareness, which makes the strategic activation of these representations unlikely (Brysbaert, 2001;Brysbaert et al, 1999;Deacon et al, 2000;Drieghe and Brysbaert, 2002;Ferrand and Grainger, 1994;Kiefer and Spitzer, 2000;Lukatela and Turvey, 1994;Ortells et al, 2016;Wheat et al, 2010).…”
Section: Introductionmentioning
confidence: 90%